The Analysis Of Consumption Pattern Of Household The Oil Palm Farmers In Labuhanbatu Regency - Nasution, Zulkarnain (Publisher Cv. Inara, 2021)
The aim of this research is to recognize the income variable, the economic activity, and the family size determination, also differences in the location of living against oil palm farmer consumption in Labuhanbatu Regency, Indonesia. The Method that used to analyze the data is Multiple Linear Regression model, specified in Least Square Dummy Variable (LSDV) method. The estimation result found that all of independent variable positive significantly influenced the food consumption. Otherwise, the negative one significantly influenced the non-food consumption outcome. The estimation result also found that the level of consumption for many kinds of urban food was fewer than hinterland society food consumption about Rp.1.248.000. However, the urban consumption more excessively than coastal area society about Rp.1.323.000. While the level of consumption outcome for many kinds of non-food urban consumption larger than non-food hinterland consumption about Rp.2.248.000. Also larger than non-food coastal society consumption about Rp.1.376.000. The variation of independent variable capability to explain the food consumption about 92,5 % and non-food consumption outcome about 87,4 %. The specification models were appropriated which the model free of multicollinearity and Heteroscedasticity classic assumption collision.